Outdoor unit for refrigeration cycle device - HIRASAWA YUTA (2024)
An outdoor unit of a refrigeration cycle device according to an embodiment of the present invention comprises: a housing; a plurality of compressors that constitute a refrigeration cycle provided inside the housing; a compressor cover configured in a box shape by a plurality of surfaces and covering the plurality of compressors; a plurality of injection pipes through which a part of the refrigerant of the refrigeration cycle flows into each compressor; and a pipe extraction opening which is formed by cutting the lower end portion of any one of the plurality of surfaces of the compressor cover and is used for extracting the plurality of injection pipes from the inside of the compressor cover to the outside, and the plurality of injection pipes are arranged side by side in the longitudinal direction relative to the pipe extraction opening. 本发明实施方式所涉及的制冷循环装置的室外机包括：壳体；多个压缩机，其构成设置在壳体内的制冷循环；压缩机盖，其通过多个面构成为箱状并覆盖多个压缩机；多个注入配管，其使制冷循环的制冷剂的一部分流入各压缩机；以及配管取出口，其对压缩机盖的多个面的任一个面的下端部进行切口而形成，并用于将多个注入配管从压缩机盖的内部取出到外部，多个注入配管相对于配管取出口